Design and fabrication of flexible rack for lecturer use - Abdul Zarif, Abdul Malek (2007)
The study of manufacturing was very important in order to carry out this project to ensure that student understand on what are needs to do. This project is about designing and fabricating the flexible rack for lecturer use to helps lecturer storing documents or paper works in their office more efficiently. This project involves the process of designing the rack by considering the shape and also the ergonomic factor for lecturer to use. After the design has completed, it was transformed to its real product where the design is used for guideline. This project also required analysis to make sure the strength of the product to ensure the safety for the user indeed of publishing. Numerous methods and process involve in this; project for instance shaping using bending machine. This project is mainly about generating a new concept of rack that would make storing documents at limited space become easier and more efficient. After all the process had been done, this rack may help us to understand the fabrication and designing process that involved in this project.